Assessment of Disturbances across Forest Inventory Plots in the Southeastern United States for the Period 1995–2018. Issue 2 (26th November 2019) - Ojha, Santosh K; Naka, Kozma; Dimov, Luben D
Abstract: Disturbances of varying frequency and intensity shape the species composition, stand structure, and functions of forests. This study assessed the frequency and distribution of disturbances caused by eight agents (insects, diseases, fire, animals, weather, other vegetation, human, and unknown) in the forests of the southeastern United States from 1995 to 2018. We used data from 88, 722 inventory measurements of 33, 531 plots from the USDA Forest Inventory and Analysis database to assess disturbance among different forest types and to different canopy strata. Disturbances were detected in approximately 14 percent of the plots, located mostly in pine-dominated forest types. Fire was the most frequent disturbance agent (occurring 6 percent of the time), followed by weather and animal agents. The agents that caused the highest mortality rate during the period for saplings were silvicultural treatments (8.6 percent), other vegetation (5.6 percent), and fire (4.4 percent), whereas for trees they were silvicultural treatments (9.8 percent), weather (1.9 percent) and insects (1.7 percent). The forest type that appeared to have been most affected by disturbances was longleaf–slash pine of the Coastal Plain. These results are useful for understanding the spatiotemporal distribution of disturbance events in different southeastern forest types and locations and for guiding forest management activities to mitigate potential impacts.